The consumption and reggaeton´s language under debate among adolescents - González Gómez , Isabel; Delgado-García, Manuel (Linguo Didáctica, 2022)
Music is not just a simple pastime, as it also contributes to the construction of identities, promotes cultural development or generates close affective ties between those who share the same musical preferences. In recent years, reggaeton has become very popular, a musical genre admired by youth and characterized by containing, in its lyrics, discriminatory messages towards women. In this sense, it is vitally important to question the impact exerted on adolescents, where it has penetrated with greater impetus, analyzing the possible consequences that it may have when building or reinforcing macho thoughts. A qualitative research is proposed that tries to examine the perceptions of adolescents. Through two focus groups, the opinions of young people enrolled in the educational stages of 2nd ESO and 3rd ESO from two secondary education institutes in the province of Huelva are debated and confronted. During the focus group sessions, the participants question the relationship between different variables that emerge from the properties of the language used in some reggaeton lyrics, such as machismo or gender violence. The analysis of the speeches derived from the work sessions has been developed through the Maxqda software. The results reveal a type of music that is expanding as a trend among adolescents, whose messages are not clearly discriminated or prosecuted and which tend to normalize certain discriminatory behaviors towards women and reinforce macho thinking among the male gender. For all these reasons, the educational system must promote the creation of a musical culture that invites adolescents to be aware of and critically judge the music they listen to daily.